Integrasi Nasional untuk Keutuhan Bangsa Indonesia - Intan Siti Nurfadilah; Anida Hanif Nurfitri (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2025)
Indonesia, as a multicultural archipelagic country, has a big challenge in maintaining the integrity of the nation's unity. Ethnic, cultural, religious, and linguistic diversity is a wealth and a potential for conflict if not managed properly. This article aims to examine how national integration can strengthen the integrity of the Indonesian nation as well as the factors that affect the success of the process. Through the literature review method, this article analyzes the concepts, theories, and determinants of national integration. The results of the study show that national integration plays an important role in strengthening national identity, minimizing social conflicts, and maintaining political stability. Therefore, synergy between elements of the nation is the key to strengthening unity in globalization and global challeng